Refleksi Pembelajaran Daring Berorintasi Kearifan Lokal dan Penilaian Teman Sebaya - Gusti Ayu Mahayukti; Gede Suweken (Universitas Pendidikan Ganesha, 2022)
This study aims to improve the character and achievement of students' mathematics learning through online learning oriented to local wisdom and peer assessment. This research is collaborative action research for 12 weeks with two teachers. The subjects of this study were students as many as 61 people. The object studied in this study was the positive character of students including curiosity, critical attitude, and discipline, in the learning process. The instruments used in this research were lesson plans, scoring rubrics, observation sheets, and mathematics learning achievement tests. This research was carried out in 2 Cycles. Student character data was collected using observation sheets and learning achievement was collected by learning achievement tests. To see the validity of the instrument after being used, an expert test was conducted by two lecturers. Data on the character of each student were obtained based on the score from the calculation of points obtained through the observation sheet. Data from observations and learning achievement tests were analyzed descriptively. The results showed that online learning oriented to local wisdom with peer assessment succeeded in improving students’ character and learning achievement in mathematics. Furthermore, there were also some obstacles in learning such as 5% of students who were late in submitting assignments and there were students who did not join virtual face-to-face meetings or during discussions through WAG.